2001
DOI: 10.1002/1521-3951(200111)228:2<453::aid-pssb453>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indium Segregation and Well-Width Fluctuations on Optical Properties of InGaN/GaN Quantum Wells

Abstract: We report the results of calculations for the energies of confined electrons and holes and their wavefunction overlap in In x Ga 1--x N/GaN quantum wells (QWs) with an indium concentration of x = 15% in the well material. It is known that the observed increase in the photoluminescence lifetime with increasing well width can be explained qualitatively by the reduction in overlap of the electron and hole wave functions, which is caused by the piezoelectric field in the strained QW material. We show that the ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been proved via both transmission electron microscope and atom probe tomography that there are one-/two-monolayer high islands on the top of the InGaN QW interface while the bottom interface of the QW being smooth [40][41][42]. Calculations have shown that, due to the in-built electric field along the growth direction, these monolayer well-width fluctuations have a strong effect that decreases the transition energy by about 60 meV in typical green or blue QWs [41,43], which may again localise carriers.…”
Section: Carrier Localisationmentioning
confidence: 99%
“…It has been proved via both transmission electron microscope and atom probe tomography that there are one-/two-monolayer high islands on the top of the InGaN QW interface while the bottom interface of the QW being smooth [40][41][42]. Calculations have shown that, due to the in-built electric field along the growth direction, these monolayer well-width fluctuations have a strong effect that decreases the transition energy by about 60 meV in typical green or blue QWs [41,43], which may again localise carriers.…”
Section: Carrier Localisationmentioning
confidence: 99%